Ciclismo: mulher e sociabilidade em Belém do Pará ao final do século XIX - LOBO, Louise Barbosa (2022)
The historical-temporal focus of the research was the city of Belém do Pará, between the decades of 1870 and 1890, a period that covers part of the Amazonian Belle Époque. By choosing belenense women as the subject of the research, cycling was adopted as the guiding thread, aiming to understand this practice as a participant in the insertion of those women in the world of sociability inherent to an ongoing urbanization dynamic. The research was of a historical and documentary nature, and its methodology implied the definition of the collection, as well as the selection, cataloging, handling and analysis of documentary sources, namely, belenense newspapers from the period mentioned here. Were discussed forms of sociability of the woman from Belém from the 1870s, culminating with the arrival of cycling in the city and the participation of women in the beginning of this practice. It was concluded that the insertion of women in cycling as sociability occurred, initially, in the form of spectator and, in a second moment, as a participant in cycling tours, and then, finally, presenting themselves as an athlete.